DAMPAK INOVASI PEMASARAN TERHADAP STRUKTUR MODAL DAN KINERJA PERUSAHAAN - Djoko Wintoro (University of Merdeka Malang, 2008)
Marketing innovation was important to companies which competed in the basis ofinnovation. The degree of marketing innovation, however, depended on the availability offinancial slack to the company. By using financial data of firms listed at JSX, this studyinvestigated the impact of the decision of marketing innovation on the decision of capitalstructure and performance. The finding showed that the degree of marketing innovation hadimpact on the level of capital structure and the degree of performance.